Impact of sand surface coating on biocementation mechanisms - Vilar, Rayla; Ikuma, Kaoru; Cetin, Bora (Frontiers in Materials, 2025)
In biocementation, the overall degree of cementation achieved is constrained by the successful completion of four individual, potentially rate-limiting steps: (i) adsorption of the biocatalyst urease onto the soil grains, (ii) retained enzymatic activity of adsorbed urease, (iii) calcium carbonate (CaCO3) precipitation, and (iv) soil strengthening. Failure in any single step can result in no or limited cementation thus limited strength gain. This study conducted a thorough analysis of each step and how they translated to the degree of cementation achieved in mixtures of uncoated, iron-coated, and hydrophobically treated sand. Our results showed that higher levels of protein adsorption and urease activity were found in columns containing 10% hydrophobic sand, but that did not translate to higher amounts of calcium precipitate produced. Approximately 23% more protein mass adsorbed onto the iron-coated columns compared to 100% sand columns, but the overall urease activity was similar among these columns. However, the strength gain was 100% higher in the iron-coated columns when compared to 100% sand columns, suggesting that CaCO3 bridging was highly effective in the iron-coated columns. Overall, the results from this study highlight the importance of considering each underlying mechanisms behind biocementation, especially when the goal is to optimize the technique for field applications.